Zika Virus Induced More Severe Inflammatory Response Than Dengue Virus in Chicken Embryonic Livers - Zhang, Zongyi; Sun, Menghan; Deng, Jieping; Yu, Jianhai; Yang, Xuesong; Zhao, Wei; Chen, Guobing; Wang, Pengcheng (Frontiers in Microbiology, 2019)
Dengue (DENV) and Zika virus (ZIKV) are important flaviviruses in tropical and subtropical regions, causing severe Dengue Hemorrhagic Fever (DHF)/Dengue Shock Syndrome (DSS) and microcephaly, respectively. The infection of both viruses during pregnancy were reported with adverse fetal outcomes. To investigate the effects of ZIKV and DENV infections on fetal development, we established an infection model in chicken embryos. Compared with DENV-2, the infection of ZIKV significantly retarded the development of chicken embryos. High viral loads of both DENV-2 and ZIKV was detected in brain, eye and heart 7 and 11 days post infection, respectively. Interestingly, only ZIKV but not DENV-2 was detected in the liver. Even both of them induced apparent liver inflammation, ZIKV infection showed a more severe inflammatory response than DENV-2 infection based on the inflammation scores and the gene expression levels of IL-1β, TNF-α, IL-6 and TGF β -2 in liver. Our results demonstrated that ZIKV induced more severe inflammatory response in chicken embryo liver compared to DENV-2, which might partially attribute to viral replication in liver cells. Clinicians should be aware of the potential liver injury associated with ZIKV infection in patients, especially in perinatal fetuses.